(untitled) (Architecture Image Studies, 2026)
Having optimal backhand punch performance is the goal of an athlete. The role of the coach is a very important part of the effort to provide programs to improve backhand shots in amateur athletes to achieve the expected achievements. One of them is by paying attention to the integral components of the backhand shot. This study aims to determine the effect of agility and arm power on backhand drive in students of Physical Education, Health and Recreation, Sebelas Maret University, Surakarta. This study uses a quantitative method with a correlational approach. Based on statistical analysis, it was found that there is a correlation between agility and arm power on backhand drive, this can be seen from the results of the correlation test with SPSS 22,There is a significant relationship between arm agility and the results of tennis backhand drive strokes, as evidenced by the calculation table г ≥ г or0.926 > r table 0.576. There is a significant relationship between arm explosive power and tennis backhand groundstroke results, as evidenced by the calculated γ value ≥ γ table or 0.789 >0.576 years. Based on the results of the study, it can be concluded that the Pearson correlation in this analysis is positive, which means that the relationship between the two variables is positive, or in other words, the greater the increase in agility and arm strength, the greater the result of tennis backhand drive strokes. The implications of this study lie in the role of trainers in determining the influence on the agility and strength components on the arm muscles. So that this can be a solution for coaches in an effort to increase backhand shots in amateur athletes.